Muslim-Christian dialogue in post-colonial Northern Nigeria : the challenges of inclusive cultural and religious pluralism - Iwuchukwu, Marinus C.; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2013)
Iwuchukwu examines the perennial conflicts in different parts of northern Nigeria and why they are popularly called Muslim-Christian clashes. Specifically, he examines the immediate and remote factors that are responsible for the conflicts.
Keywords: Religion; Islam; Religion -- History; Religion and sociology; World history; Philosophy